What I saw and how I lied - Blundell, Judy. (Scholastic Press, 2008)
In 1947, with her jovial stepfather Joe back from the war and family life returning to normal, teenaged Evie, smitten by the handsome young ex-GI who seems to have a secret hold on Joe, finds herself caught in a complicated web of lies whose devastating outcome changes her life and that of her family forever.